PENGGUNAAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN AGAMA KATOLIK UNTUK MENINGKATKAN PENALARAN KRITIS SISWA - Siska Sinaga; Erikson Simbolon; Zulfi Ambriano Banurea (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This research is motivated by the low critical reasoning ability of students in Catholic Religious Education learning, which is still dominated by lecture methods and passive learning. This study aims to analyze the use of the Problem-Based Learning (PBL) model in improving the critical reasoning ability of grade X phase E students at SMA Santa Maria Kabanjahe. The research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The research participants consisted of the principal, Catholic Religious Education teacher, and students involved in the implementation of the Problem-Based Learning (PBL) model. The data is analyzed through the stages of data reduction, data presentation, and conclusion drawing, and its validity is tested using source and technique triangulation. Research results indicate that the implementation of the PBL model can enhance students' active involvement in the learning process, encourage the ability to analyze information, express opinions logically, reflect on learning materials, and connect Catholic faith teachings with everyday life. The improvement in students' critical reasoning skills was reflected in their ability to obtain and process information, analyze problems, reflect on their thinking, make decisions, and draw logical conclusions. In addition, the PBL model helps students become more independent, collaborative, and reflective in solving learning problems. Therefore, the implementation of Problem Based Learning is effective in supporting the development of students' critical reasoning in Catholic Religious Education and is relevant to be used as a student-centered learning approach in the implementation of the Merdeka Curriculum. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan penalaran kritis siswa dalam pembelajaran Pendidikan Agama Katolik yang masih didominasi metode ceramah dan pembelajaran pasif. Penelitian ini bertujuan untuk menganalisis penggunaan model Problem Based Learning (PBL) dalam meningkatkan kemampuan penalaran kritis siswa fase E kelas X di SMA Santa Maria Kabanjahe. Penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Informan penelitian terdiri atas kepala sekolah, guru Pendidikan Agama Katolik, dan siswa yang terlibat dalam penerapan model Problem Based Learning (PBL). Data dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan, serta diuji keabsahannya menggunakan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa penerapan model PBL mampu meningkatkan keterlibatan aktif siswa dalam proses pembelajaran, mendorong kemampuan menganalisis informasi, mengemukakan pendapat secara logis, merefleksikan materi pembelajaran, serta menghubungkan ajaran iman Katolik dengan kehidupan sehari-hari. Peningkatan kemampuan penalaran kritis terlihat pada kemampuan siswa memperoleh dan mengolah informasi, menganalisis masalah, merefleksikan pemikiran, serta mengambil keputusan dan menarik kesimpulan secara logis. Selain itu, model PBL membantu siswa lebih mandiri, kolaboratif, dan reflektif dalam menyelesaikan permasalahan pembelajaran. Dengan demikian, penerapan Problem Based Learning efektif dalam mendukung pengembangan penalaran kritis siswa pada pembelajaran Pendidikan Agama Katolik dan relevan digunakan sebagai pendekatan pembelajaran yang berpusat pada peserta didik dalam implementasi Kurikulum Merdeka.